The moderating role of employees’ professionalism on BSC usage and organizational performance relationship - Bakil Saleh Mohamad Dhaifallah,; Sofiah Md Auzair,; Ruhanita Maelah, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Innovations in management accounting practices require placing more comprehensive integrated performance measures to improve performance. Although there is evidence on the practice of balanced scorecard (BSC) in Malaysia, little is known about the influence of BSC usage to organizational performance and factors that improves this relationship. This paper examines the moderating effect of employees’ professionalism on the relationship between BSC usage and organizational performance. A questionnaire survey was administered to chief financial officers (CFOs) of Malaysian manufacturing firms. Using 110 responses, the findings indicate that professionalism of staffs significantly enhanced the relationship between BSC usage and organizational performance. Specifically, the findings suggest that social obligation dimension strengthens the implication of using the firms’ BSC.